2018
DOI: 10.1002/cmdc.201800481
|View full text |Cite
|
Sign up to set email alerts
|

Identification of α‐Mangostin as an Agonist of Human STING

Abstract: The xanthone derivate 5',6'-dimethylxanthenone-4-acetic acid (DMXAA, also known as ASA404 or vadimezan) is a potent agonist of murine STING (stimulator of interferon genes), but cannot activate human STING. Herein we report that α-mangostin, which bears the xanthone skeleton, is an agonist of human STING, but activates murine STING to a lesser extent. Biochemical and cell-based assays indicate that α-mangostin binds to and activates human STING, leading to activation of the downstream interferon regulatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 36 publications
1
65
0
Order By: Relevance
“…Meanwhile, Yibo Zhang et al identified a-Mangostin (Fig. 3g) sharing the same xanthone skeleton with DMXAA as a weak agonist of hSTING [141]. These findings provide a critical guide for future rational drug design of DMXAA variants with potential to enhance the interferons production in humans, which are needed for the development of anticancer therapies and vaccine adjuvants.…”
Section: Dmxaa and Its Analoguesmentioning
confidence: 91%
“…Meanwhile, Yibo Zhang et al identified a-Mangostin (Fig. 3g) sharing the same xanthone skeleton with DMXAA as a weak agonist of hSTING [141]. These findings provide a critical guide for future rational drug design of DMXAA variants with potential to enhance the interferons production in humans, which are needed for the development of anticancer therapies and vaccine adjuvants.…”
Section: Dmxaa and Its Analoguesmentioning
confidence: 91%
“…Presently, there are eleven examples of non-CDN agonists ( Table 1 ), a majority of which share structural similarities with DMXAA ( Figure 5 ) [ 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. GlaxoSmithKline (GSK) identified small molecule STING agonists, which shared a vital amidobenzimidazole component [ 91 ].…”
Section: Sting Activating Drugsmentioning
confidence: 99%
“…Unlike the previous compounds, the remaining three compounds are capable of stimulating the human STING pathway. α‐Mangostin (Figure ), bearing a xanthone skeleton, was reported by Quan et al to have better human STING activity over that of mouse STING . BNBC and diABZI were identified via high‐throughput screening (HTS).…”
Section: Sting Agonistsmentioning
confidence: 99%